Evaluating the Therapeutic Impact of Exercise on Chronic Diseases: A Comprehensive Review and Future Directions - Liu Ai Dong (International Journal of Education and Humanities, 2024)
This study aims to evaluate the therapeutic benefits of exercise interventions for chronic diseases, including cardiovascular diseases, hypertension, diabetes, and cancer. The research involves a comprehensive analysis of the scope, application, and challenges associated with various exercise therapy programs, providing valuable insights for clinical practice and future research. Data were sourced from the WHO website, Web of Science, and several databases, such as PubMed, Embase, CNKI, Wipu, Zhi.com, and Wanfang, employing keywords like "chronic disease," "exercise therapy," "intervention effect," "cardiovascular disease," "hypertension," "diabetes," and "malignant tumor." The review reveals that exercise can prevent several types of cancer and enhance the survival rates of patients with breast, colon, and prostate cancers. Specifically, aerobic exercise has been shown to significantly improve cardiac function in patients with cardiovascular diseases, reduce blood pressure in those with hypertension, and lower the incidence of diabetes among middle-aged and elderly populations. These findings underscore the critical role of exercise in managing and potentially preventing chronic diseases, thereby improving patients' quality of life and survival outcomes. Furthermore, the study highlights the need for greater dissemination of knowledge regarding the benefits of exercise for chronic disease management. It also emphasizes the importance of integrating big data technologies into the comprehensive management of exercise therapy, enabling personalized and effective treatment plans. Overall, this study advocates for the incorporation of exercise therapy into standard medical care practices to mitigate the burden of chronic diseases